Nasal Carriage of Mycoplasma spp. and Mycoplasma bovis in Healthy Calves - Derya Karataş Yeni; Muhammed Can Gökmen; Fatih Büyük; Aslı Balevi (Animal Health Production and Hygiene, 2026)
Mycoplasma spp., particularly Mycoplasma bovis, are important pathogens of bovine respiratory disease and can colonize both clinically affected and healthy calves subclinically. This highlights the importance of detecting these agents in healthy herds to prevent silent transmission within the herd. This study aimed to investigate the presence of Mycoplasma spp. in the nasal flora of clinically healthy calves raised in Ereğli and Karapınar districts of Konya, Türkiye, using both cultural and molecular methods. Among 198 nasal swab samples, 28 (14.1%) were positive for Mycoplasma spp. by culture, and 20 of these isolates (71.4%) were confirmed by genus-specific PCR, resulting in a molecular prevalence of 10.1%. Species-specific PCR analysis identified 25% of the culture- and genus-specific PCR-positive isolates as Mycoplasma bovis, corresponding to an overall nasal swab prevalence of 2.53%. No statistically significant differences in culture or PCR positivity were observed among the different farms (P>0.05). The findings indicate that Mycoplasma spp. and M. bovis can be present in the nasal flora of clinically healthy calves, demonstrating subclinical carriage and the potential for silent herd transmission, providing valuable information for epidemiological monitoring and risk-based control strategies.